Energy efficiency in the private rental sector in Victoria, Australia: When and why do small-scale private landlords retrofit?. (June 2022) - Lang, Michaela; Lane, Ruth; Zhao, Kun; Raven, Rob
Abstract: Energy efficiency in private rental properties is lower than that of owner-occupied homes. As landlords are the primary decision-makers for improving rental properties, understanding their energy efficiency behaviour is critical to improving the uptake of energy efficiency retrofits in the private rental sector. However, little is known about how landlords make decisions about energy efficiency retrofits. The study aims to understand when and why landlords decide to retrofit and identify policy implications, using the private rental sector in Victoria as a case study. The results show that proactive retrofitting by landlords is rare and that the retrofits undertaken were generally low-cost, incremental energy efficiency improvements. Most retrofit activity was prompted by government subsidies, tenant requests, or appliance breakdown. Despite its significance for energy efficiency, retrofitting behaviour was not related to environmental values. Instead, landlords considered financial implications and tenants' needs. However, landlords who used property managers had little understanding of tenants' needs. Policymakers can use this understanding of landlords' behaviour by creating new retrofit prompts and highlighting the impacts of energy inefficiency on tenants' wellbeing. Transitioning the private rental sector to low-energy housing requires integrated policy to change the behaviour of landlords, tenants, and property managers.